2-Naphthylmethyl N-[1-(4-pyridyl)ethylidene]hydrazinecarbodithioate. - How, Fiona Ni Foong; Watkin, David J.; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim (International Union of Crystallography, 2007)
The molecules in the crystal structure of the title compound, C19H17N3S2, are linked by an intermolecular N-H...N [2.839 (5) Å] hydrogen bond via the [alpha]-N and the pyridyl N atoms. The thione S atom is in a trans position with respect to the methylpyridine fragment across the C-N bond but adopts a cis position with respect to the naphthalene ring across the C-S bond. There is a [pi]-[pi] stacking interaction between the naphthalene rings, with a centroid-centroid distance of 3.397 (2) Å.